Acute effects of mango leaf extract on cognitive function in healthy adults: a randomised, double-blind, placebo-controlled crossover study - Fiona L. Dodd; David O. Kennedy; Jodee Johnson; Emily Haworth; Emily Haworth; Jessica P. Greener; Philippa A. Jackson (Frontiers in Nutrition, 2024)
IntroductionExtracts made from the leaves of the edible mango plant (Mangifera indica L., Anacardiaceae) have a long history of medicinal usage, most likely due to the presence of high levels of mangiferin, a polyphenol compound. Previous research has demonstrated that mango leaf extract (MLE) can beneficially modulate cognitive function in both animals and humans. This study aimed to assess the effects of an acute dose of 300 mg MLE (standardised to contain ≥60% mangiferin) on cognitive performance and mood in healthy adults.MethodsIn this double-blind, placebo-controlled, crossover study, 114 healthy men and women (18–43 years) received either MLE or a matched placebo at each testing visit (separated by at least 7 days). Cognitive performance (including the cognitive demand battery) and mood were measured at 30, 180, and 300 min post-dose.ResultsThe results showed that, compared to placebo, the group taking MLE displayed a significant increase in serial 3 s and serial 7 s subtraction errors overall. There were no other significant effects on cognitive performance.DiscussionThe results of the current study suggest that the consumption of 300 mg MLE in the absence of an observed multitasking psychological stressor does not improve cognitive performance or mood at up to 300 min post-dose. Due to the very limited nature of the effects and since they were observed among many analyses, these findings should be treated with caution.Clinical trial registration: http://ClinicalTrials.gov, identifier [NCT05182450].